2016
DOI: 10.1249/mss.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Physical Activity and Adulthood Earnings

Abstract: The findings provide evidence that childhood physical activity can have far-reaching positive effects on adulthood earnings. Possibilities for improving physical activity during childhood may not only promote health but also affect long-term labor market outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 40 publications
2
21
1
Order By: Relevance
“…Globally, it is estimated that the direct costs attributable to physical inactivity range from 0.3% to 4.6% of national healthcare expenditures. 1,2 Additionally, studies in this field have found that physical activity is related to rewards in the labor market, such as higher earnings [3][4][5][6][7][8][9][10][11] and higher probability of employment 8,12,13 (see Appendix 1 for a literature summary).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, it is estimated that the direct costs attributable to physical inactivity range from 0.3% to 4.6% of national healthcare expenditures. 1,2 Additionally, studies in this field have found that physical activity is related to rewards in the labor market, such as higher earnings [3][4][5][6][7][8][9][10][11] and higher probability of employment 8,12,13 (see Appendix 1 for a literature summary).…”
Section: Introductionmentioning
confidence: 99%
“…Rooth 10 also showed that individuals who indicate in job applications that they are physically active have a higher probability of receiving callbacks to job interviews. Cabane and Clark 14 and Kari et al 5 are examples of studies that have analyzed the role of childhood physical activity instead of adulthood physical activity in various labor market outcomes. In sum, Cabane and Clark 14 did not find an association between childhood sporting activities and earnings, job satisfaction, and the probability of being a worker, whereas Kari et al, 5 on the other hand, did document a positive association between childhood leisure-time physical activity and earnings in adulthood, especially among men.…”
Section: Introductionmentioning
confidence: 99%
“…One could be that the women with Externalizing behaviors were physically more active than the other women. A high level of physical activity already during adolescence has been found to reduce job strain [37] and increase earnings [38] in adulthood, and to increase/ maintain work ability in the general population [39]. On the other hand, the relevance of psychosocial problems to labor market inclusion might depend on concurrent unhealthy behaviors, as the Multiple risk behavior cluster associated significantly with over one year of unemployment, and the men in the Externalizing behavior class smoked the most.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of studies makes comparison of findings difficult. Only studies that have analyzed physical activity in childhood and in adulthood 16 , in adolescence and adulthood 17 and physical activity in different phases of life can be found in literature 9 .…”
Section: Discussionmentioning
confidence: 99%